(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
A study has been analysed the “Impact of core banking solutions in public sector bank comparison with HDFC bank.” There is no significant relationship between customers perception towards dimensions of service quality of core banking solutions offered by public sector and private banks. A method was used to random sample was conducted on 2 respondents selected from Bhagalpur district and the primary data was collected from 60 respondents (customers) of core banking solutions, public sector and HDFC banks selected from Bhagalpur district. In order to draw the conclusion, the primary data collected through interview schedule from the customers of core banking, public and sector banks comparison with HDFC bank and analysed with the help of statistical tools. The study reveals the respondents positively view about the core banking services offered by public and HDFC bank respondents positively view about the customers using selected channel of core banking services towards public bank and HDFC bank.